Parkinson's disease and gait asymmetry - Barbieri, Fabio A. [UNESP]; Fiorelli, Carolina Menezes [UNESP]; Penedo, Tiago [UNESP]; De Paula, Pedro Henrique Alves [UNESP]; Simieli, Lucas [UNESP]; Moretto, Gabriel Felipe [UNESP]; Imaizumi, Luis Felipe Itikawa [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Springer Nature, 2017)
Walking is considered symmetric in neurologically healthy individuals. However, asymmetry begins to occur with aging, and could be indicative of neurodegenerative diseases, such as Parkinson's disease (PD). The aim of this chapter is to discuss gait asymmetry in people with PD. Specifically, we present a general idea about unilateral signs/symptoms of PD and its influence on asymmetry and review the literature about unobstructed gait asymmetry in people with PD. Finally, we show the effects of obstacle crossing and auditory cues on gait asymmetry in people with PD. Previous studies have indicated that people with PD presented greater asymmetry in the temporal parameters compared to neurologically healthy older subjects. For obstacle crossing during walking, both people with PD and neurologically healthy older individuals demonstrated a higher symmetric index for step duration during obstacle crossing while walking compared to unobstructed walking. Therefore, obstacle avoidance increases gait asymmetry of neurologically healthy older individuals and people with PD. Auditory cues decreased asymmetry for step length, duration and velocity, and cadence in individuals with PD compared to neurologically healthy older individuals. However, only neurologically healthy older individuals demosntrated greater asymmetry in the trials with auditory cues for step length, duration and velocity, and cadence. Therefore, auditory cues seem to have no effects on gait asymmetry for unobstructed and obstacle walking in individuals with PD, and impair gait asymmetry in neurologically healthy older individuals during obstacle avoidance.
Keywords: Aging; Asymmetry; Auditory cues; Obstacle avoidance; Parkinson's disease; Sidedness; Walking